First detection and complete genome of Soybean chlorotic mottle virus naturally infecting soybean in China by deep sequencing - Qian-qian HU; Xue-jian LIU; Xue-dong HAN; Yong LIU; Jun-xi JIANG; Yan XIE (Journal of Integrative Agriculture)
Soybean chlorotic mottle virus (SbCMV) was first detected from soybean plants in Jiangxi Province of China by high throughput sequencing and was confirmed by PCR. The complete nucleotide sequence of NC113 was determined to be 8 210 nucleotides, and shared the highest similarity (91.7%) with sequences of SbCMV that was only reported in Japan. It encodes nine putative open reading frames (ORFs Ia, Ib and II–VIII), and contains a large intergenic region located at nucleotide 5 976–6 512 between ORFs VI and VII. Sequence analysis and phylogenetic tree indicated that NC113 is an isolate of SbCMV, and is more related to the soymoviruses Blueberry red ringspot virus (BRRSV), Peanut chlorotic streak virus (PCSV) and Cestrum yellow leaf curling virus (CmYLCV) than to other representative members in the Caulimoviridae family. Field survey of 472 legume plants from Jiangxi and Zhejiang provinces showed SbCMV was only detected from soybean in Nanchang City with a low incidence rate. This is the first report of Soybean chlorotic mottle virus identified in China.